Zahn-Wellens test in industrial wastewater biodegradability assessment = Test Zahn-Wellensa w ocenie biodegradowalności ścieków przemysłowych - Płuciennik-Koropczuk, Ewelina; Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Biodegradability of pollution contained in examined industrial wastewater was assessed according to methodology based on Zahn-Wellens (OECD 302B) test. The following kinds of wastewater were examined: metal industry wastewater from aluminium pressure foundry; wastewater from industrial waste treatment processes, such as: filtration waste, chemical reagents, coolants, water emulsions, oil wastes and other industrial wastes, galvanising waste treatment processes sludge.
Keywords: COD; organic substances; industrial wastewater; liquids; ChZT; substancje organiczne; ścieki przemysłowe; odcieki